Change emergencies: between the traditional pedagogical model and the necessity of significant learnings - Ana Martínez Vélez (Universidad del Magdalena, 2014)
The central intention of this writing is to share with the readers some vicissitudes felt and lived by teachers and students who day to day face the task of wanting to learn, and the eagerness to teach. They share, live and coexist in the way of the education of the professional accounting, although not always in equal spheres, but they coexistence with the same educative problems, they are derived from the pedagogical practices that they are manage into the academic programs of public accountant.